UPAYA PENINGKATAN PEMBELAJARAN SEPAKBOLA MENGGUNAKAN PERMAINAN SEPAKBOLA MINI PADA SISWA KELAS V SDN GAJI 1 KECAMATAN GUNTUR KABUPATEN DEMAK TAHUN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This study aims to improve the learning outcomes of football using mini football game in the fifth grade students of SDN Salary 1 Guntur districts Demak Year 2012/2013. To obtain the appropriate data in this study using PTK (Classroom Action Research). For TOD shapedÂ  cycle assessment process, which uses two cycles and consists of four stages: planning, action, observation and reflective. The research instrument using the check list to record the attitudes and events that occur in learning deemed important and have been set will be investigated. From the observations obtained with the help of a check list can be obtained that percentage aspects of psychomotor skills, cognitive, and affective of the fifth grade students of SDN Guntur District Salaries 1 Demak regency after learning given an increase, in the first cycle and second cycle percentage has increased from 73 , 9% to 86.4%. As well as the percentage of completeness in the first cycle only reached 57.1% of the number of students there. And the second cycle increased to 92.9%. Thus the act of learning by applying football mini football game in the fifth grade students of SDN Salary 1 Demak district Guntur District was successful.